Estimation of Risk Factors for Head Slippage Using a Head Clamp System. A Retrospective Study - Sakakura K; Fujimoto A; Ichikawa N; Ishikawa E; Matsumura A; Enoki H; Okanishi T (Dove Medical Press, 2020)
Kazuki Sakakura,1,2 Ayataka Fujimoto,1 Naoki Ichikawa,1 Eiichi Ishikawa,2 Akira Matsumura,2 Hideo Enoki,1 Tohru Okanishi1 1Comprehensive Epilepsy Center, Seirei Hamamatsu General Hospital, Hamamatsu, Shizuoka, Japan; 2Department of Neurosurgery, University of Tsukuba, Tsukuba, Ibaraki, JapanCorrespondence: Ayataka FujimotoSeirei Hamamatsu General Hospital, 2-12-12 Sumiyoshi, Nakaku, Hamamatsu, Shizuoka 430-8558, JapanTel +81-53-474-2222Fax +81-53-475-7596Email afujimotoscienceacademy@gmail.comBackground: Although complications have been associated with head clamp systems, few reports have described head slippage. The present study aimed to determine risk factors for head slippage and speculated that the position of head holder pins might be associated.Patients and Methods: We reviewed medical records and compared the positions of the pinned heads of patients on fused preoperative and postoperative computerized tomography (CT) images. We measured the distance between corresponding head pins to determine head slippage. Age, sex, body weight, body mass index, surgical position, surgical duration, craniotomy volume, and the relationship between head pins and the nasion-inion (NI) line were statistically compared between patients with and without head slippage.Results: Head slippage in 3 (10%) of 28 patients was significantly associated with the most caudal pin position (p < 0.001) and craniotomy volume (p = 0.036). Receiver operator characteristics curves indicated a cutoff of 4.5 cm from the NI line (sensitivity and specificity, 1.000 and 0.800, respectively).Conclusion: Clamped heads can slip during surgical procedures. We found that one head pin should be located within 4.5 cm from the NI line to avoid head slippage.Keywords: head movement, mayfield head clamp, intraoperative computed tomography, nasion-inion line, pinning